Being with the ‘Other’: inter-religious marriages in Bangladesh - Rahman, Fahmida (BRAC Univeristy, 2017)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2016.